Structure and plant diversity in area of cerradão in the Municipality of Jerumenha - Piauí (Research, Society and Development, 2020)
The Cerrado has high plant diversity, however, it is one of the most threatened biomes on the planet, being considered as one of the priority areas for conservation. In this sense, o objective was to evaluate the floristic and structural diversity of an area of ​​the Cerrado of future expansion of silviculture, at Fazenda Campeira, municipality of Jerumenha-PI. The forest inventory was carried out in 10 plots (20 x 50m). Phytosociology was assessed using individuals with DNS ≥ 3cm. for phytosociology and individuals in the vicinity or below the inclusion criteria for floristics, with measures of total height also being observed. 55 species were found, of these, 42 sampled in the phytosociological survey. The most representative species were: Fabaceae (198), Vochysiaceae (127) and Malpighiaceae (77) individual. The most important species were: Pouteria ramiflora (Mart.) Radlk.; Qualea parviflora Mart.; Byrsonima crassifolia (L.) Kunth.; Plathymenia reticulata Benth.; Pterodon abruptus (Moric.) Benth. The average height of the specimens was 4.54 ± 2.55m and the diametric structure was 12.25 ± 9.95cm. The density and basal area values ​​were 724 ind.ha-1 and 15, 874 m²/ha, respectively, with a Shannon diversity index (H') was 3.22 nats/ind. The region showed high diversity and considering the advance of deforestation in the region, taxonomic and ecological knowledge of these areas is necessary, as it is possible to glimpse measures for the recovery and conservation of the cerrados.